The antioxidant and antimutagenic activities of Cyclopia spesies and activity-guided fractionation of C. intermedia - Richards, Elizabeth Siân (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc )--Stellenbosch University, 2003.